ANALISIS KELAYAKAN USAHA TEMPE DI DESA SUKAMAJU KECAMATAN SUKAMAJU, KABUPATEN LUWU UTARA - -, Intisari (Jurnal Ilmiah Ecosystem, 2016)
This study aims to analyze the feasibility of tempe in Sukamaju village, District Sukamaju, North Luwu.Intake of respondents in this study using census method, which takes all those who seek tempe in Sukamaju village, District Sukamaju, North Luwu, amounting to eight people. Analysis of the data used in this research is the analysis of R / C Ratio and BEP analysis.The results showed that the soybean business in Sukamaju village to be developed either from the analysis of R / C Ratio and of BEP analysis. Based on the analysis of R / C Ratio obtained a value of 2.92 which means that the business is feasible to be developed because the value of R / C ratio is greater than one. BEP Analysis of results showed that the average amount of production per one production per respondent is 659,99buah greater (>) than with the BEP production (units) that is equal to 7.00021 fruit. Similarly, the calculation results BEP receipts (IDR) also shows that businesses in the village Sukamaju tempe feasible to be developed, because the average amount of revenue (USD) per one production per respondent is Rp. 1.467.661,29lebih large (>) compared with BEP receipts (IDR) Rp. 15566.82006.